Increased expression of NAMPT in PBMC from patients with acute coronary syndrome and in inflammatory M1 macrophages. Issue 1 (November 2015) - Halvorsen, Bente; Espeland, Martine Z.; Andersen, Geir Øystein; Yndestad, Arne; Sagen, Ellen Lund; Rashidi, Azita; Knudsen, Eva C.; Skjelland, Mona; Skagen, Karolina R.; Krohg-Sørensen, Kirsten; Holm, Sverre; Ritschel, Vibeke; et al.
Abstract: Aim: The aim of the present study were to elucidate the role of NAMPT in atherosclerosis, by examine NAMPT expression in peripheral blood mononuclear cells (PBMC) in patients with coronary artery disease (CAD) and healthy controls and by examining the regulation and effect of NAMPT on macrophage polarization, hypothesizing that it could influence the polarization to inflammatory and resolving macrophages. Method and Results: We analyzed RNA levels of NAMPT in PBMC from CAD and healthy controls and found NAMPT to be increased in PBMC from patients with acute coronary syndrome (n = 39) compared to healthy controls (n = 20) and patients with stable CAD (n = 22). Within the PBMC NAMPT was correlated to several inflammatory cytokines and the antioxidant enzyme superoxide dismutase 2. In vitro cell experiments revealed that NAMPT is increased both intracellular and extracellular in inflammatory M1 macrophages compared to in anti-inflammatory M2 macrophages. In addition, inhibiting NAMPT enzymatic activity inhibited M1 polarization in macrophages. Conclusion: Based on our in vivo and in vitro findings we suggest that NAMPT could contribute to systemic and plaque inflammation in atherosclerotic disorders at least partly through effect on macrophages. Highlights: NAMPT expression is increased in PBMC from patients with CAD. NAMPT expression correlates with inflammatory markers and redox regulation in PBMC from CAD patients. NAMPT expression is increased in inflammatory (M1) macrophages. Nampt expression increases during inflammatory macrophage polarization. NAMPT inhibition pushes the macrophage towards a less inflammatory phenotype.